Asas Netralitas ASN dalam Pemilihan Kepala Daerah Tahun 2020: Studi Kasus di Kabupaten Maros - Agussalim A. Gadjong (SIGn Jurnal Hukum, 2021)
This study aims to examine and analyze the implementation, prevention, forms of violations, and factors influencing the ASN Neutrality principle in the 2020 Regional Head Elections in Maros Regency. This study uses empirical research methods. Primary data collection is done by direct interviews. The data obtained in this study were then analyzed qualitatively to analyze the problem and answer the research objectives. The results showed that the neutrality of civil servants in implementing the 2020 Regional Head Elections in the Maros Regency had not been carried out correctly. The worst condition was because three unscrupulous employees violated ASN neutrality more than once. Meanwhile, Bawaslu has taken various forms of efforts to prevent violations related to ASN Neutrality in Maros Regency: through coordination and outreach meetings, letters of appeal, and visual aids. The factors that influence the neutrality of ASN in the holding of Regional Head Elections: are patron-client culture, primordial (kinship relations), law enforcement, and motivation for positions. Therefore, it is recommended that the Ministry of Internal Affairs increasingly consider the principle of neutrality in the selection process for ASN candidates. In addition, it is recommended that KASN provide strict sanctions for ASN who are not neutral. In this case, in the future, there will be no more violations of ASN neutrality that are committed more than once.